The environment in world history - Mosley, Stephen (Themes in world history., 2010)
"Covering the past 500 years of global history, The Environment in World History examines the processes that have transformed the earth and have put growing pressure on natural resources." "The Environment in World History also examines how European expansion overseas brought about a fundamental reorganisation of the world's ecology as contact between long-isolated continents was re-established. It offers a fresh environmental perspective on familiar world-history narratives of imperialism and colonialism, trade and commerce, and technological progress and the advance of civilisation, and will be invaluable reading for all students of world history and environmental studies."--BOOK JACKET.